Growth performance of tiger grouper juveniles (Epinephelus fuscoguttatus forsskal) with varying stocking densities in open flow-through and closed systems - Salari, Reza (2013)
Two tests were carried out in the present research work to examine the influence of the nursery rearing period as a critical phase on minimizing the cannibalism issue in the aquaculture industry. The relationship between a range of stocking densities and fish growth rates in different flow-through conditions of water (open flow-through and closed-system) was additionally scrutinized. The aim was to determine the optimum stocking density and appropriate water flow system for E. fuscoguttatus juveniles to survive. Observations were made from December 2010 to February 2011 at the Marine Finfish Production and Research Center, Tg. Demong, Besut, Terengganu. The purpose of the initial experiment was to study how various stocking densities in open flow-through water affect the critical rearing phase of tiger grouper juveniles. The densities studied are 1fish/l (T1), 3fish/l (T2), and 5fish/l (T3). Following the 42-day nursery stage, the fish grown in the T2 condition had the top final mean body weight (10.45±0.17g), as well as the utmost total length (84.92±3.04mm). The variation noted with respect to the Specific Growth Rate, Feed Conversion Ratio,Daily Weight Gain and Protein Efficiency Ratio between T2 and the other treatments was P<0.05. The outcome of this experiment therefore indicates that fish stocked at a density of 3 fish per liter demonstrated enhanced size frequency, growth and final biomass in contrast to the other two stocking densities. Yet, negligible statistical disparities of P>0.05 were noted for the condition and survival rearing among various treatments during six nursery weeks in the open flow-through water system. A separate trial assessed the effects of varying stocking densities in the critical developing stage of E. fuscogattatus juveniles in a closed system. To determine the aptness in nursing early juveniles leaving the hatchery, the three grouper juvenile treatments utilized in this second experiment were 1fish/l (T1), 3fish/l (T2) and 5fish/l (T3). After 42 culture days in the closed system experiment, differences found for weight, length, and other growth parameters of fish reared at 1, 3 and 5fish/l were insignificant at P>0.05. The growth of young grouper juveniles in various nursery culture systems was recorded following 42 days of tending. Generally, according to the results, the final mean body weight and total length, Specific Growth Rate and Feed Conversion Ratio were numerically superior in the open flow-through structure, with 10.45±0.17g,84.92±3.04mm, 13.05±0.12% and 1.22±0.04 in contrast to the closed system, in which the values were 6.90±0.19g, 69.42±1.37mm, 12.17±0.44% and 1.38±0.03, respectively. Besides, in the flow-through water system, the fish grew at a higher rate numerically (0.184-0.25g.f-1d-1) than those in the closed system (0.160-0.164 g.f-1d-1). No difference in the development and survival of fish in both system densities was noted. This study thus recommends the use of an open flow-through system for culturing tiger grouper juveniles, as it seems to be more efficient than a closed system.